Innocent Bystanders : Developing Countries and the War on Drugs - Keefer, Philip (Washington, DC: World Bank and Palgrave Macmillan, 2012)
Drug use and abuse is one of the most difficult challenges facing the contemporary world. If it is true that there has always been consumption of different types of drugs in different societies, although not in all of them, it is no less true that it generally took place in restricted, socially regulated realms, especially in ritualistic ceremonies. This is not the case today. Drug use has spread to all segments of society, with hedonistic motivations; although it is often not socially sanctioned, users are at times, depending on the drug, treated with leniency. It is well-established that all drugs are harmful to the health, even the legal ones, such as alcohol and tobacco, and that some drugs are more harmful, such as heroin and crack. The discussion of 'gateway drugs' is a medical issue on which there is no consensus. For the purposes of public policy design, the important thing to keep in mind is that drugs produce negative consequences for both users and societies in general, and that minimizing their consumption should be the main goal. The salient discussion, therefore, is about choosing among different strategies to achieve the same goal. Most of all, this book contributes to the debate by shedding light on the understanding of the economics and logistics of the drug market.